2020
DOI: 10.1021/acs.analchem.0c03134
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Labeling Proteomics Allows a High-Throughput Investigation of Protein Corona Orientation

Abstract: The formation of the biomolecular corona represents a crucial factor in controlling the biological interactions and trafficking of nanomaterials. In this context, the availability of key epitopes exposed on the surface of the corona, and able to engage the biological machinery, is important to define the biological fate of the material. While the full biomolecular corona composition can be investigated by conventional bottom-up proteomics, the assessment of the spatial orientation of proteins in the corona in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…Particularly, the authors demonstrated that isobaric labeling of proteins in the PC with subsequent analysis of MS/MS spectra of tryptic peptides represent an easy and high-throughput way to study the orientation of the proteins in the original corona. 109…”
Section: Proteomics In Nanotechnologymentioning
confidence: 99%
“…Particularly, the authors demonstrated that isobaric labeling of proteins in the PC with subsequent analysis of MS/MS spectra of tryptic peptides represent an easy and high-throughput way to study the orientation of the proteins in the original corona. 109…”
Section: Proteomics In Nanotechnologymentioning
confidence: 99%
“…Although Tf in the protein corona of CRT-MMB4@MDZ is not superior than that in the protein corona of MMB4@MDZ, CRT-MMB4@MDZ exhibited better brain-targeting effect. In recent years, researches about the spatial organization of protein coronas have come out and the randomly oriented corona proteins have been reported (Kelly et al, 2015 ; Liessi et al, 2021 ). It is reasonable to speculate that the Tf molecules bind on MMB4@MDZ with random orientation, resulted in only part of the Tf molecules orienting their TfR-binding sites to the outer-surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, protein corona analysis data after incubation of GBMs with human plasma can be used in enrichment analysis to identify alterations in biological processes and molecular functions. [ 184 ]…”
Section: Computational Approaches For Sbd Of Gbmsmentioning
confidence: 99%